2021
DOI: 10.1002/jbio.202000459
|View full text |Cite
|
Sign up to set email alerts
|

Optical incoherent technique for noninvasive assessment of blood flow in tissues: Theoretical model and experimental study

Abstract: Laser noninvasive methods for assessment of a tissue blood flow (BF), for example, the Laser Doppler Flowmetry (LDF), are well-known today. However, in such methods, low-frequency fluctuations (LFFs) in the registered optical signal caused by blood volume changes inside a tissue have not been studied in details until now. The aim of this study is to investigate the LFFs formation and to justify the LFFs-based diagnostic technique for cutaneous BF assessment. LFFs are theoretically described and experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In addition, because of the probe design, the signal is analyzed from a larger area of skin (~25 mm 2 ). Due to this, the signal backscattered from the tissue is collected from a larger tissue volume than in LDF and includes deeper vascular plexuses and larger vessels [ 14 , 15 ]. This also reduces the impact of local vascular network heterogeneity on measurement variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, because of the probe design, the signal is analyzed from a larger area of skin (~25 mm 2 ). Due to this, the signal backscattered from the tissue is collected from a larger tissue volume than in LDF and includes deeper vascular plexuses and larger vessels [ 14 , 15 ]. This also reduces the impact of local vascular network heterogeneity on measurement variability.…”
Section: Discussionmentioning
confidence: 99%
“…The prototype device uses three LED emission sources operating in the wavelength range of 560–580 nm and one silicon photodiode in the optical sensor. The perfusion value calculated during signal processing is similar to that in laser Doppler flowmetry (LDF) [ 15 , 19 ]. The method allows the assessment of perfusion measured in perfusion units (PU).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of methods allowing non-invasive assessment of skin microcirculation include laser Doppler flowmetry (LDF), laser speckle-contrast imaging (LSCI), novel method of incoherent optical fluctuation flowmetry (IOFF), capillaroscopy, etc. [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that despite almost half a century of history of using the LDF method in microcirculation research, it is still not used in clinical practice. Recently, Lapitan and Rogatkin suggested that the reason for LDF drawbacks is more fundamental and related to the nature of coherent light used in this technique [ 27 ]. To improve the performance of an optical technique in a blood flow assessment, they proposed the use of incoherent light, as is commonly used in the photoplethysmography (PPG) method.…”
Section: Introductionmentioning
confidence: 99%